Inovasi Pembelajaran Interaktif REACT: Strategi Efektif untuk Meningkatkan Keterampilan Menulis Mahasiswa - Zuve, Farel Olva; Fadhil, A-Syifa Rumaysah; Ananda, Refisa (Lingua Susastra, 2024)
This study examines the impact of the REACT (Relating, Experiencing, Applying, Cooperating, Transferring) model on the writing skills of university students. The research objectives were to describe students' writing skills before and after using the REACT model and to investigate the model's effect on their writing performance. The study employed a quasi-experimental design with a non-equivalent control group. The sample consisted of 40 undergraduate students enrolled in an English writing course. The experimental group (n = 20) received writing instruction using the REACT model, while the control group (n = 20) received traditional writing instruction. Pre-test and post-test writing assessments were used to evaluate students' writing skills. The results showed that the experimental group’s writing skills improved from a mean score of 56.94 (SD = 8.12) in the pre-test to 75.88 (SD = 6.45) in the post-test, indicating a significant improvement from a “Fair” to a “More than sufficient” level. The control group's mean scores were 55.78 (SD = 7.89) and 61.23 (SD = 8.01) in the pre-test and post-test, respectively. A paired t-test revealed a statistically significant difference between the pre-test and post-test scores of the experimental group (t(19) = 4.39, p .05), suggesting that the REACT model had a positive impact on students' writing skills. These findings highlight the potential of the REACT model as an effective instructional approach for enhancing writing skills in university students.